Strategi Pengembangan Potensi Wisata Svarga Minapadi di Desa Panembangan Kecamatan Cilongok Kabupaten Banyumas: Development Strategy of Svarga Minapadi Tourism Potential in Panembangan Village Cilongok District Banyumas Regency - Rokhani, Andi; Sutikno, Chamid; Pribadi, Indah Ayu Permana; Millata, Chanifia Izza; Amanda, Ariesta (Journal of Community Development and Disaster Management, 2025)
This study examines the Strategy for Developing the Potential of Panembangan Village, Cilongok District, Banyumas Regency. The research method used is a qualitative method with descriptive analysis. The data sources used are primary and secondary data collected through observation, interviews, and documentation. The theory used is the strategic management theory according to Fred R David (2011) which has three stages, namely strategy formulation, strategy implementation, and strategy evaluation. The results of the study indicate that at the strategy formulation stage, the vision and mission are not yet available, causing medium-term and long-term goals to not be implemented. In addition to these conditions, developing alternative strategies and choosing appropriate strategies for Svarga Minapadi tourism has not been implemented. At the strategy implementation stage, setting annual goals in Svarga Minapadi tourism is carried out through a short-term plan for allocating village funds to build tourism facilities. Sustainable policies and resource allocation have been implemented through the development of new destinations in the form of Minapadi Technopark and Panembangan Aquatic. At the strategy evaluation stage, reviewing internal and external factors has not been implemented consistently by Svarga Minapadi tourism. Performance can be measured by the number of visitors and income which tend to increase and are stable. Corrective actions can be taken by improving facilities and adjusting strategies that can be implemented through monthly evaluation forums.